Reverse shoulder arthroplasty: clinical results and quality of life evaluation - Arnaldo Amado Ferreira Neto; Eduardo Angeli Malavolta; Jorge Henrique Assunção; Evelinda Marramon Trindade; Mauro Emilio Conforto Gracitelli (Revista Brasileira de Ortopedia)
ABSTRACT OBJECTIVE: To evaluate the clinical and radiological results and the impact on quality of life of the reverse shoulder arthroplasty. METHODS: Retrospective case series evaluating 13 patients undergoing reverse shoulder arthroplasty with at least two years of clinical follow-up. Clinical evaluation was performed before and after surgery with the ASES and VAS scales and hand-mouth, hand-neck, and hand-head functional tests. Quality of life was measured with the SF-12 questionnaire. The rate of complications and radiographic postoperative findings were recorded. RESULTS: The patients improved from 23.1 ± 15 to 82.7 ± 15 according to ASES scale (p < 0.001). The physical component of the SF-12 increased from 31.7 ± 6.9 to 47.1 ± 8.6 (p < 0.001), while the emotional increased from 48 ± 12.3 to 55.5 ± 7.5 (p = 0.061). The pain reduced from 7.9 to 1 according to the VAS (p = 0.002). The performance on the hand-mouth, hand-neck, and hand-head functional tests showed significant improvement (p = 0.039, p < 0.001 and p < 0.001, respectively). Complications occurred in 15% of patients and notching, in 31%. CONCLUSION: Reverse shoulder arthroplasty led to a significant clinical improvement according to the ASES and VAS scales. The quality of life has improved according to the physical aspect of the SF-12, and showed a trend of improvement in the emotional aspect. The complication rate was 15%, and notching occurred in 31%.